Pisa Syndrome in Parkinson’s Disease: Electromyographic Aspects and Implications for Rehabilitation - Giuseppe Frazzitta; Pietro Balbi; Francesco Gotti; Roberto Maestri; Annarita Sabetta; Luca Caremani; Laura Gobbi; Marina Capobianco; Rossana Bera; Nir Giladi; Davide Ferrazzoli (Parkinson's Disease)
Pisa Syndrome (PS) is a real clinical enigma, and its management remains a challenge. In order to improve the knowledge about resting state and during maximal voluntary muscle contraction (MVMC) of the axial muscles, we described the electromyography results of paraspinal muscles, rectus abdominis, external oblique, and quadratus lumborum of both sides of 60 patients. Electromyography was assessed at rest, during MVMC while bending in the opposite direction of the PS and during MVMC while bending in the direction of the PS. The MVMC gave information about the interferential pattern (INT) or subinterferential pattern (sub-INT). We defined asymmetrical activation (AA) when a sub-INT was detected on the muscle on the side opposite to the PS bending and an INT of same muscle in the direction of PS bending. We observed significant AA during MVMC only in the external oblique muscles in 78% of the subjects. Our results of asymmetric ability to generate maximal voluntary force of the external oblique muscles support a central dissynchronisation of axial muscles as a significant contributor for the bending of the spine in erect position. These results could have important implication to physiotherapy and the use of botulinum toxin in the treatment of PS.